If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 1 = -2x + -1 + 1 Reorder the terms: 1 + -3x = -2x + -1 + 1 Reorder the terms: 1 + -3x = -1 + 1 + -2x Combine like terms: -1 + 1 = 0 1 + -3x = 0 + -2x 1 + -3x = -2x Solving 1 + -3x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + -3x + 2x = -2x + 2x Combine like terms: -3x + 2x = -1x 1 + -1x = -2x + 2x Combine like terms: -2x + 2x = 0 1 + -1x = 0 Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| -2(3s-4)-8=-3(5s+5)-5 | | 20(x)=25(1) | | -2(3x-4)-8=-3(5x+5)-5 | | (3/x)*5x | | 2m+m+m+2=w+18 | | 25(1)=20(x) | | 3(x+3)-7x=5 | | 3m+5=m+9 | | 0.30(24)+0.05x=0.10(12+x) | | 0.90x+0.05(14-x)=0.10(-61) | | -4u^2+u+3=0 | | 0.8=[3.6/1][8.5/21000] | | 0.8=[DeltaQ/1][8.5/21000] | | 4+3f-2f+f=f+5 | | 4x-5=3x-(8) | | 4x+5=3x-(8) | | 4+3f-2+f=f+5 | | 3x^2/3-11x^1/3=-10 | | 4x+x-15+3-8=13 | | 144+x=180 | | 9.5+e=14.7 | | x-1=1.03-1 | | 3X-40+2N=15 | | b^10/b^2 | | 500+.13+2= | | 4(2)(5)= | | 3y=-4/2 | | a(x+1)+b(x-1)=1 | | a(x+1)+b(x-1)= | | 29+r=240 | | ax+a+bx-b=1 | | m^2+2m-120=0 |